2012
DOI: 10.3389/fphar.2012.00186
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Effect of Nicotine Intake on Neuroplasticity in Non-Smoking Humans

Abstract: In various studies nicotine has shown to alter cognitive functions in non-smoking subjects. The physiological basis for these effects might be nicotine-generated modulation of cortical structure, excitability, and activity, as mainly described in animal experiments. In accordance, a recently conducted study demonstrated that application of nicotine for hours via nicotine patch in non-smoking humans alters the effects of neuroplasticity-inducing non-invasive brain stimulation techniques on cortical excitability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 49 publications
2
29
0
7
Order By: Relevance
“…In the intervention groups receiving either prolonged nicotine patch application (Thirugnanasambandam et al, 2011) or fast-acting nicotine nasal spray application (Grundey et al, 2012a), the results of these studies showed a reduced or abolished LTD-like neuroplasticity response following cathodal tDCS. With regard to our findings in healthy smokers, one comparable study showed a significant MEP reduction Smoking restores LTD-like plasticity in schizophrenia W Strube et al following cathodal tDCS in healthy subjects under nicotine withdrawal for 10 h, but only a trendwise MEP reduction following nicotine patch application (Grundey et al, 2012b). As in our experimental setup, only a short period of nicotine withdrawal preceded the experiments and these subjects displayed related LTD-like plasticity responses, as did healthy subjects following prolonged nicotine patch application (Grundey et al, 2012b), so one might argue that our withdrawal duration may be insufficient to restore nicotine-related abolishment of plasticity.…”
Section: Smoking Effect On Tdcs-induced Neuroplasticity In Healthy Sumentioning
confidence: 76%
See 3 more Smart Citations
“…In the intervention groups receiving either prolonged nicotine patch application (Thirugnanasambandam et al, 2011) or fast-acting nicotine nasal spray application (Grundey et al, 2012a), the results of these studies showed a reduced or abolished LTD-like neuroplasticity response following cathodal tDCS. With regard to our findings in healthy smokers, one comparable study showed a significant MEP reduction Smoking restores LTD-like plasticity in schizophrenia W Strube et al following cathodal tDCS in healthy subjects under nicotine withdrawal for 10 h, but only a trendwise MEP reduction following nicotine patch application (Grundey et al, 2012b). As in our experimental setup, only a short period of nicotine withdrawal preceded the experiments and these subjects displayed related LTD-like plasticity responses, as did healthy subjects following prolonged nicotine patch application (Grundey et al, 2012b), so one might argue that our withdrawal duration may be insufficient to restore nicotine-related abolishment of plasticity.…”
Section: Smoking Effect On Tdcs-induced Neuroplasticity In Healthy Sumentioning
confidence: 76%
“…With regard to our findings in healthy smokers, one comparable study showed a significant MEP reduction Smoking restores LTD-like plasticity in schizophrenia W Strube et al following cathodal tDCS in healthy subjects under nicotine withdrawal for 10 h, but only a trendwise MEP reduction following nicotine patch application (Grundey et al, 2012b). As in our experimental setup, only a short period of nicotine withdrawal preceded the experiments and these subjects displayed related LTD-like plasticity responses, as did healthy subjects following prolonged nicotine patch application (Grundey et al, 2012b), so one might argue that our withdrawal duration may be insufficient to restore nicotine-related abolishment of plasticity. The effects in smokers might therefore be at least partially determined by an impact of nicotine.…”
Section: Smoking Effect On Tdcs-induced Neuroplasticity In Healthy Sumentioning
confidence: 76%
See 2 more Smart Citations
“…In fact, the investigation by several research groups about the effect of nicotine on attention (Kadir et al, 2006) and learning and memory have given heterogeneous results (Smith et al, 2006). Grundey et al (2012) show new evidence of a negative effect of nicotine spray on facilitatory plasticity and a diminished reduction in excitability after transcranial direct current stimulation. These results differ from the effects observed after chronic nicotine administration.…”
mentioning
confidence: 99%